2021
DOI: 10.1021/jacs.1c02428
|View full text |Cite
|
Sign up to set email alerts
|

Capturing the Missing Carbon Cage Isomer of C84 via Mutual Stabilization of a Triangular Monometallic Cyanide Cluster

Abstract: Monometallic cyanide clusterfullerenes (CYCFs) represent a unique branch of endohedral clusterfullerenes with merely one metal atom encapsulated, offering a model system for elucidating structure–property correlation, while up to now only C82 and C76 cages have been isolated for the pristine CYCFs. C84 is one of the most abundant fullerenes and has 24 isomers obeying the isolated pentagon rule (IPR), among which 14 isomers have been already isolated, whereas the C 2v (17)-C84 isomer has lower relative energy t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 59 publications
0
23
0
Order By: Relevance
“…Monometallic cyanide clusterfullerene (CYCF), YCN@ C s (6)-C 82 , was first reported by Yang and co-workers in 2013 . So far, a series of lanthanide based CYCFs have been synthesized, isolated, and characterized, including MCN@ C 2 v (19138)-C 76 (M = Y, Tb, and Lu), , YCN@ C s (6)-C 82 , MCN@C 84 (M = Y, Tb, Dy), and MCN@C 82 (M = Tb, Lu, and Dy). ,− One exceptional feature of the encapsulated MCN clusters is their structural flexibility, which can exist as either triangular or nearly linear geometries inside different fullerene cages. Thus, it is intriguing to explore the possibility of entrapping an actinide cyanide cluster into a fullerene cage, which could lead to new understanding for the binding modes of cyanide with actinide ions.…”
Section: Introductionmentioning
confidence: 99%
“…Monometallic cyanide clusterfullerene (CYCF), YCN@ C s (6)-C 82 , was first reported by Yang and co-workers in 2013 . So far, a series of lanthanide based CYCFs have been synthesized, isolated, and characterized, including MCN@ C 2 v (19138)-C 76 (M = Y, Tb, and Lu), , YCN@ C s (6)-C 82 , MCN@C 84 (M = Y, Tb, Dy), and MCN@C 82 (M = Tb, Lu, and Dy). ,− One exceptional feature of the encapsulated MCN clusters is their structural flexibility, which can exist as either triangular or nearly linear geometries inside different fullerene cages. Thus, it is intriguing to explore the possibility of entrapping an actinide cyanide cluster into a fullerene cage, which could lead to new understanding for the binding modes of cyanide with actinide ions.…”
Section: Introductionmentioning
confidence: 99%
“…suggests that the encapsulated mononuclear clusters are all located on the mirror planes of fullerene cages (see Figure 3). 5,11,[42][43][44][45] Previous studies of monometallic fullerenes (only one metal ion inside the cage) have found that in fullerene cages containing symmetry planes, the metal prefers to occupy a symmetric arrangement with respect to the interacting motifs, which share one of their symmetry planes with the fullerene. 34 This observation further suggests that the endohedral mononuclear cluster also prefers to share a symmetry plane with the fullerene cages.…”
Section: Chemical Science Accepted Manuscriptmentioning
confidence: 99%
“…[10][11][12][13] Factors such as different carbon cage isomers, the size of the carbon cage and the metal ionic radii of encapsulated clusters can all lead to changes in the cluster configuration. [14][15][16][17][18] For instance, as the size of the carbon cage decreases, M 2 C 2 clusters change from a nearly linear stretched geometry to a constrained "butterfly" structure, whereas MCN clusters change from a nearly linear shape to a triangular configuration. 13,19,20 Moreover, in non-IPR (isolated pentagon rule) carbon cages, clusters can be deformed to obtain stronger interactions with the carbon cage due to the high local strain of the heptagon or fused pentagons, thus stabilizing these carbon cages.…”
Section: Introductionmentioning
confidence: 99%